Analisis Daya Saing Produk Batik Kampung Laweyan dan Kauman Surakarta di Masa Pandemi Covid-19 - Dinna Riana (Journal of Indonesian Science Economic Research, 2020)
At the time of the Covid-19 pandemic, the batik industry in Surakarta fell drastically, efforts are needed so that Batik, which is the mainstay of Surakarta City, can still produce and maintain its competitiveness both at home and abroad. This study aims to analyze the effect of venture capital, price, network on the competitiveness of batik products in Kauman Village and Laweyan Village, Surakarta City. The research subjects were Batik industry players in the Laweyan Batik Village and Kauman Batik Village, Surakarta City. The sampling technique used was purposive multistage random sampling, the number of samples was 50 respondents. Data were collected through a questionnaire. This research uses path analysis method. The results of the analysis show that the business capital and the price partially do not have a significant effect on the entrepreneurial skills produced by batik craftsmen; Entrepreneurial networks and skills partially have a significant effect on the competitiveness of batik craftsmen products; Networks have an influence on product competitiveness through entrepreneurial skills. Variable networks that can build entrepreneurial skills which will further increase the competitiveness of batik craftsman products in Laweyan and Kauman Villages.